Variation in physicochemical properties and bioactivities of Morinda citrifolia L. (Noni) polysaccharides at different stages of maturity - Cai, Jinlin; Liang, Zijian; Li, Jian; Manzoor, Muhammad Faisal; Liu, Hongsheng; Han, Zhong; Zeng, Xinan (Frontiers in Nutrition, 2023)
Introduction Morinda citrifolia L. (Noni) as an evergreen plant is a rich source of natural polysaccharides. Objective The present work aims to investigate the maturation-related changes in polysaccharides of Morinda citrifolia L. (Noni) at five stages of maturity (stages from the lowest to highest degree – 1, 2, 3, 4, and 5). Methods The chemical composition (carbohydrate, protein, uronic acid, and sulfate radical) of Noni polysaccharides was determined by different chemical assays. Ion chromatography system was used to analyze the monosaccharide composition, and the molecular weight was measured by HPGPC. The polysaccharides were also analyzed by FT-IR and their radical scavenging effect against DPPH, hydroxyl radicals and ABTS was evaluated. The UV-vis assay and gel electrophoresis assay were performed to investigate the DNA damage protective effect. Results Results indicated the significant effect of fruit maturities on the extraction yields, molecular weights, uronic acid contents, sugar levels, monosaccharide compositions and proportions, antioxidant capacities, and DNA protective effects of Noni polysaccharides. However, no fruit maturity stage had prominent impact on the sulfuric radical contents and preliminary structure characteristics. Noni polysaccharides extracted at stage 5 (N5) had the largest extraction yield (8.26 ± 0.14%), the highest sugar content (61.94 ± 1.86%) and the most potent scavenging effect on DPPH (IC50: 1.06 mg/mL) and ABTS (IC50: 1.22 mg/mL) radicals. The stronger DPPH and ABTS radical scavenging activities of N5 might be contributed by its higher content of fucose and rhamnose and smaller molecular weight. Noni polysaccharides extracted at stage 4 (N4) showed the highest uronic acid content (4.10 ± 0.12%), and the superior performance in scavenging hydroxyl radicals and protecting DNA. The greater hydroxyl radical scavenging effect of N4 might be attributed to its higher percentage of the low molecular weight counterpart. Moreover, the DNA protective effects of N4 displayed a positive correlation with its hydroxyl radical scavenging ability. Conclusion Overall, stage 4 and stage 5 could be ideal stages of fruit maturity aiming at high-quality Noni polysaccharides extraction. This study provided valuable information for the selection of suitable Noni polysaccharides to cater for various industrial applications.